PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA BOOKLET DILENGKAPI QUIZIZZ TERHADAP HASIL BELAJAR SISWA DI SMA NEGERI 2 WAINGAPU - Paulina Luhi, Bellavista; Makaborang, Yohana; Rambu Hada Enda, Riwa (Universitas Cokroaminoto Palopo, 2024)
This study aims to find out the extent to which the Problem Based Learning model, equipped with booklet and Quizizz media, affects student learning outcomes, especially at SMA Negeri 2 Waingapu. This type of research is experimental research with a quantitative approach. This study featured two classes: class XI-2 as the control group and class XI-1 as the experimental group. The stages of data analysis in this study include validity test, reliability test, normality test, homogeneity test, and hypothesis test through the parametric method, namely the dependent sample t-test, using SPSS software. The dependent sample t-test for hypothesis testing yields Asym results. The significance (2-tailed) is 0.001, indicating that the value is below 0.05. In conclusion, H1 was accepted by H0 fans, indicating the influence of the Problem Based Learning method, facilitated by the booklet media and supplemented by Quizizz, on the learning outcomes of students at SMA Negeri 2 Waingapu.